Proses dan Etika Mujadalah dalam Al-Qur’an sebagai Pendekatan Komunikasi Dakwah - Fakhri Yusuf; Yusran Nasir; Rasyidah; Siti Maisarah; Jailani Ahmad (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2025)
This paper aims to find out the mujadalah communication approach in the Al-Qur'an. In writing, a qualitative descriptive communication approach is used with content analysis. The information collection method or technique uses library research, where library research is investigate is the movement of collecting materials related to inquire about beginning from books, journals, literature and other publications. There are two sources of data, namely primary data comes from the Al-Qur'an and Tafsir, and secondary data comes from books and other publications. The research results show that the word mujadalah comes from the Arabic